2015
DOI: 10.3109/02713683.2015.1016179
|View full text |Cite
|
Sign up to set email alerts
|

GSTM1andGSTM5Genetic Polymorphisms and Expression in Age-Related Macular Degeneration

Abstract: Purpose Previously, two cytosolic antioxidant enzymes, Glutathione S-transferase Mu 1 (GSTM1) and Mu 5 (GSTM5), were reduced in retinas with Age-related Macular Degeneration (AMD). This study compared genomic copy number variations (gCNV) of these two antioxidant enzymes in AMD vs. controls. Methods Genomic copy number (gCN) assays were performed using Taqman Gene Copy Number Assays (Applied Biosystems) in technical quadruplicate for both GSTM1 and GSTM5. Peripheral leukocyte RNA levels were compared to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The most striking effect of prenatal Pb exposure was the significant lower levels of 5hmc in the conserved genes GSTM1 (13%) and GSTM5 (21%). These genes are highly involved in the detoxification of electrophilic compounds like carcinogens, therapeutic drugs and environmental toxicants [62]. Also of interest, the gene ontology of the genes implicated in the DMRs of 5mc in males fell mainly into the functional categories of telencephalon development and glial cell differentiation, while females fell mostly into the regulation of cellular division.…”
Section: Prenatal Exposure To Pb and Bpa In Humansmentioning
confidence: 99%
“…The most striking effect of prenatal Pb exposure was the significant lower levels of 5hmc in the conserved genes GSTM1 (13%) and GSTM5 (21%). These genes are highly involved in the detoxification of electrophilic compounds like carcinogens, therapeutic drugs and environmental toxicants [62]. Also of interest, the gene ontology of the genes implicated in the DMRs of 5mc in males fell mainly into the functional categories of telencephalon development and glial cell differentiation, while females fell mostly into the regulation of cellular division.…”
Section: Prenatal Exposure To Pb and Bpa In Humansmentioning
confidence: 99%
“…The application of the above-mentioned criteria yielded five reports. [13][14][15][16][17] Study of Hunter et al 17 had been reported two case-control groups, therefore, considered as two studies. The following data were extracted: author's name, publication year, country, ethnicity of the participants and the frequencies of the genotypes for each polymorphism in ARMD patients and control subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the null genotypes of GSTT1 and GSTM1 were associated with several multifactorial human complex diseases. [5][6][7][8][9][10][11][12] There were studies investigated the relationship between these polymorphisms and the risk of ARMD, [13][14][15][16][17] the results were inconsistent. Considering that association studies usually were done on a relatively small samples size, in order to increase the sample size and aid the generalisation of the results to larger populations, the present meta-analysis was carried out.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we did not observe a significant association between R-GSSG activity and GSH concentration in any of the tested groups; thus, the increase in R-GSSG activity in patients with AMD might be an analogous indicator of increased antioxidant activity, similarly to GPx or increased GSH transferase activity. Interestingly, conflicting results on the involvement of GSTM1 and GSTM5 (glutathione s-transferase mu 1/5) polymorphisms and gene expression in AMD pathology exist [ 51 , 52 ], once again suggesting that the necessary balance of the antioxidant system is achieved through the proper activity of several enzymes, and not a single enzyme. The tight cooperation of endogenous antioxidants is reflected in SOD activity, which functions together with GPx and CAT to convert H 2 O 2 to nontoxic products and by that protect the photoreceptors and RPE from oxidative damage [ 31 , 49 ].…”
Section: Discussionmentioning
confidence: 99%